SELF-EXPRESSION ON VIOLENCE AGAINST RACISM OF BIGGER THOMAS IN NOVEL RICHARD WRIGHT’S ENTITLED NATIVE SON - Guruh Ari Prasetyo; Rr. Arielia Yustisiana (Humaniora Scientia, 2020)
The aims of this research are (1) to describe the crimes committed by Bigger Thomas as themain character in Richard Wright’s novel entitled Native Son, and (2) to analyze the influenceBigger Thomas’ self-expression on against racismin Richard Wright’s novel entitled Native Son.The data are words, phrases, clauses, and sentences, collected by document analysis, taken froma novel entitled Native Son that is written by Richard Wright. These data are then called asquotation. The theories used to analyze the data are racism and crime. Then sociological andpsychological approaches are used to analyzed  the data in this research.  The crimes that arecommitted by Bigger Thomas in the novel are assault, negligent homicide, murder, and  fraud.The self-expressions of Bigger are hatred, fear, powerless, desperation, ashamed, and prejudice.